The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/mnras/sty1446
|View full text |Cite
|
Sign up to set email alerts
|

Merger driven star-formation activity in Cl J1449+0856 at z=1.99 as seen by ALMA and JVLA

Abstract: We use ALMA and JVLA observations of the galaxy cluster Cl J1449+0856 at z=1.99, in order to study how dust-obscured star-formation, ISM content and AGN activity are linked to environment and galaxy interactions during the crucial phase of high-z cluster assembly. We present detections of multiple transitions of 12 CO, as well as dust continuum emission detections from 11 galaxies in the core of Cl J1449+0856. We measure the gas excitation properties, star-formation rates, gas consumption timescales and gas-to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 78 publications
1
39
0
Order By: Relevance
“…That the environmental quenching efficiency for lower-M * declines rapidly over this window perhaps suggests a similar decline for higher-M * at even higher redshifts than are studied here. Such a picture is consistent with several works studying clusters at z > ∼ 1.4, in which the average star formation is seen in many cases to be unperturbed or even enhanced relative to field environments (e.g., Brodwin et al 2013;Alberts et al 2014Alberts et al , 2016Santos et al 2014;Wang et al 2016;Stach et al 2017;Coogan et al 2018).…”
Section: Environmental Quenching Efficiencysupporting
confidence: 91%
“…That the environmental quenching efficiency for lower-M * declines rapidly over this window perhaps suggests a similar decline for higher-M * at even higher redshifts than are studied here. Such a picture is consistent with several works studying clusters at z > ∼ 1.4, in which the average star formation is seen in many cases to be unperturbed or even enhanced relative to field environments (e.g., Brodwin et al 2013;Alberts et al 2014Alberts et al , 2016Santos et al 2014;Wang et al 2016;Stach et al 2017;Coogan et al 2018).…”
Section: Environmental Quenching Efficiencysupporting
confidence: 91%
“…The authors speculated that the environment of galaxy clusters helps feeding the gas through into the cluster members and reduces the efficiency of star formation. On the other hand, Coogan et al (2018) found lower τ H2 , enhanced SFE and highly excited CO SLEDs in protocluster members at z = 1.99, linking such activity to mergers. The general picture of how dense environments might or not contribute to enhance or suppress the accretion of gas and affect its efficiency to form stars is still debated and unclear.…”
Section: Gas Fractions and Star Formation Efficienciesmentioning
confidence: 88%
“…At z ∼ 1.5-2.5 several works have studied the molecular gas content, efficiency of converting gas into stars and their relation with the specific star formation rate (sSFR = SFR/M * ) and with field galaxies, those that do not necessarily live in an overdense environment (e.g., Noble et al 2017;Lee et al 2017;Rudnick et al 2017;Dannerbauer et al 2017;Hayashi et al 2018;Coogan et al 2018). In this section we explore and discuss these matters regarding our sample of protoclusters cores.…”
Section: Gas Fractions and Star Formation Efficienciesmentioning
confidence: 99%
“…More details about these ancillary data can be found in Strazzullo et al (2013), Valentino et al (2015Valentino et al ( , 2016, Coogan et al (2018), and references therein.…”
Section: Ancillary Datamentioning
confidence: 99%